2009
DOI: 10.3945/jn.108.095018
|View full text |Cite
|
Sign up to set email alerts
|

Green tea (Camellia sinensis) Attenuates Nephropathy by Downregulating Nox4 NADPH Oxidase in Diabetic Spontaneously Hypertensive Rats

Abstract: Green tea (GT), through its antioxidant properties, may be useful to treat or prevent human diseases. Because several lines of evidence suggest that oxidative stress contributes to the pathogenesis of diabetic nephropathy, we tested the hypothesis that GT prevents diabetes and hypertension-related renal oxidative stress, attenuating renal injury. Spontaneously hypertensive rats (SHR) with streptozotocin-induced diabetes and nondiabetic SHR were treated daily with tap water or freshly prepared GT (13.3 g/L). Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…67,[85][86][87][88][93][94][95][97][98][99]156 Finally, in experimental diabetes, the use of green tea was associated with an improvement in diabetic nephropathy and retinopathy and associated with a reduction in oxidative stress. 91, 157 The usefulness of these dietary approaches in diabetic patients with hypertension and nephropathy or retinopathy that are on standard treatment deserves to be tested in larger clinical trials. Finally, a better understanding and identification of the basic mechanism of action of different antioxidants in diabetes can lead to better optimization of renal and retinal protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67,[85][86][87][88][93][94][95][97][98][99]156 Finally, in experimental diabetes, the use of green tea was associated with an improvement in diabetic nephropathy and retinopathy and associated with a reduction in oxidative stress. 91, 157 The usefulness of these dietary approaches in diabetic patients with hypertension and nephropathy or retinopathy that are on standard treatment deserves to be tested in larger clinical trials. Finally, a better understanding and identification of the basic mechanism of action of different antioxidants in diabetes can lead to better optimization of renal and retinal protection.…”
Section: Discussionmentioning
confidence: 99%
“…90 In a different study, it was found that longterm green tea consumption ameliorates renal injury in hypertensive diabetic rats by inhibiting oxidative stress through downregulation of Nox4 expression. 91 The presence of hypertension exacerbates retinopathy in diabetic animals. We have demonstrated that the concomitance of both diabetes and hypertension leads to earlier and more pronounced retinal inflammatory alterations characterized by increased expression levels of ICAM-1, VEGF and NF-kB p65 in the retina when compared with those of normotensive diabetic rats.…”
Section: Inflammation and Oxidative Stress As The Underlying Mechanismentioning
confidence: 99%
“…Previous studies revealed that ECM accumulation in DN is closely associated with the activation of the p38 MAPK-signaling pathway, oxidative stress, and mitochondrial dysfunction. 16,[37][38][39][40][41] Therefore, we predict that the abnormality of DRP1 affects mitochondrial function, and further influences p38 MAPK-signaling pathways, thus affecting DN.…”
Section: Introductionmentioning
confidence: 99%
“…The samples and Western blots were prepared as described in previous studies [23,24,25]. The following primary antibodies were used: goat anti-type IV collagen (1:500, Southern Biotech, Birmingham, AL), goat anti-fibronectin (F/N) (1:500, EMD Millipore, Billerica, MA), rabbit anti-NOX4 (1:500, Santa Cruz Biotechnology, Danvers, MA), rabbit anti-alpha smooth muscle actin (α-SMA) (1:500, Abcam, Cambridge, MA), rabbit phosphorylated AMPK (Thr 172 ) and LKB1 (Ser 428 ) (1:1000, Cell Signalling Technology, Danvers, MA), rabbit total AMPK and LKB1 (1:1000, Cell Signalling Technology), rabbit phosphorylated SMAD3 (1:500, Cell Signalling Technology, Danvers, MA), and total rabbit SMAD3 (1:1000, Cell Signalling Technology, Danvers, MA).…”
Section: Methodsmentioning
confidence: 99%